2021
DOI: 10.18291/njwls.123740
|View full text |Cite
|
Sign up to set email alerts
|

Being There No Matter What: Working in Publicly Provided Homecare Services

Abstract: The aim of this article is to critically explore how formal and informal work practices interplay with gender in the shaping of homecare service’s work environments. An ethnomethodological view on doing gender is applied in combination with theories about challenges in relational work.The material is drawn from two projects represented by (i) a cooperative inquiry about Swedish homecare service’s work environments, with homecare service workers and first-line mangers (seven included in this article) and (ii) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In many places, budgetary restrictions were sensed to urge employees to prioritise certain acts 'at the expense of compassion, caring, and quality' (ibid: e6), in part because many tasks remained undone or postponed even when informal caregivers were performing tasks 'that legally are the responsibility of public services'. Vänje and Sjöberg Forssberg (2021), studying work environments in publicly provided home care services in Sweden, conveyed a similar impression. Their analysis starts with the observation that care work has become 'more intense' under the influence of 'industrial production concepts' and a steering model based on performance indicators.…”
Section: Offering Independence To Dependent People?mentioning
confidence: 81%
See 2 more Smart Citations
“…In many places, budgetary restrictions were sensed to urge employees to prioritise certain acts 'at the expense of compassion, caring, and quality' (ibid: e6), in part because many tasks remained undone or postponed even when informal caregivers were performing tasks 'that legally are the responsibility of public services'. Vänje and Sjöberg Forssberg (2021), studying work environments in publicly provided home care services in Sweden, conveyed a similar impression. Their analysis starts with the observation that care work has become 'more intense' under the influence of 'industrial production concepts' and a steering model based on performance indicators.…”
Section: Offering Independence To Dependent People?mentioning
confidence: 81%
“…While being more popular, the supply of domiciliary care has seen similar dynamics over recent decades (Bode and Streicher 2014;Hayes 2017;McDonald et al 2019;Ravalier et al 2019;Vänje and Sjöberg Forssberg 2021;Palmqvist 2022). In many parts of Europe, this sector has been found to suffer from fragmented service delivery; interrupted continuity of care; and rapid staff turnover.…”
Section: Counter-movements: Institutional Change Putting Later Life U...mentioning
confidence: 99%
See 1 more Smart Citation
“…The association of care work to femininity is not only produced by society or higher decision makers. Even though care workers and first-line managers express awareness of injustices linked to the low status and female-dominance (Lill, 2010;Vänje & Forssberg, 2021), it is also reinforced by themselves. One example is how first-line managers expect female workers to show more engagement to provide good quality of care.…”
mentioning
confidence: 99%
“…Several studies have reported that the responsibilities of firstline managers in elderly care have expanded and include more tasks (Abdelrazek, Skytt, Aly, El-Sabour, Ibrahim, & Engström, 2010;Andersson Felé, 2008). Administrative work tasks have increased in line with the decrease in administrative support (Andersson Felé, 2008;Regnö, 2021;Vänje & Forssberg, 2021). First-line managers' report that they do so-called illegitimate tasks that are not perceived as their responsibility, and that these tasks should be performed by someone else in the organisation (Björk, Bejerot, Jacobshagen, & Härenstam, 2013).…”
mentioning
confidence: 99%